ATRT-15. Primordial germ cells identified as one potential cell of origin of MYC rhabdoid tumors. (3rd June 2022) - Graf, Monika; Interlandi, Marta; Moreno, Natalia; Roy, Rajanya; Holdhof, Dörthe; Göbel, Carolin; Melcher, Viktoria; Mertins, Julius; Albert, Thomas K; Kastrati, Dennis; Alfert, Amelie; Holsten, Till; et al.
Abstract: Rhabdoid tumors (RT) are embryonal neoplasms occurring most frequently in the central nervous system where they are termed atypical teratoid rhabdoid tumor (ATRT). A common hallmark of RT is homozygous loss of the BAF complex subunit SMARCB1. RT patients have a poor prognosis with an overall survival time of 17 months and >60% of patients suffer from relapses. The lack of an optimal treatment strategy could be attributed to the heterogeneity within and between different subgroups of ATRT. Despite the recent advancements in characterizing RT at a molecular level, the cellular origin of RT remains elusive. Thus, this study focused on the identification of the cellular origin of MYC-RT and underlying epigenetic deregulations which account for the cellular heterogeneity in these tumors. We showed that Smarcb1 abrogation in Sox2 -positive progenitor cells at E6.5 give rise to RT of the MYC and SHH subgroup in genetically engineered mouse models (GEMM). To uncover distinct cells of origin (COO) for the SHH and MYC subgroups, unbiased computational approaches were used to compare single-cell transcriptomes of GEMMs with single-cell reference maps of murine early embryogenesis. While SHH tumors arise from mid/hindbrain progenitor cells, primordial germ cells (PGCs) emerge as COO of both intracranial and extracranial MYC tumors. PGCs as COO of MYC-RT were validated in vivo by using PGC-specific Smarcb1 knockout mouse model. We further characterized a deregulated transcriptome in MYC-RT compared to PGCs, which is sustained by a subset of epigenetically driven tumor cells. Deregulated expression of genes driving methylation/demethylation processes in MYC tumors and regression of these tumors upon treatment with decitabine in vitro and in vivo, indicates that DNA methylation plays a key role in cellular transformation and development of MYC-RT.